Visual endodontics curriculum - Haapasalo, M. (Markus); Quintessence Publishing Co. (Berlin ; [Chicago] : Quintessenz, 2006)
(Producer) Multimedia DVD-ROM covering the entire field of endodontics and dental trauma. Contains over 2,400 high-resolution images and over 1,400 smaller images, along with 26 digital video clips and compact sections of text
Title from disc label
System requirements for PC: Pentium-based computer with Windows 2000 (SP4) or XP; 128 MB RAM or more; DVD-ROM drive; 450 MB free space on the hard disk; graphics system with 1024x768 pixel resolution at 24 bit color depth (True Color); speakers; Internet Explorer version 6 with JavaScript enabled; Sun Java version 1.5; Quicktime version 7.
System requirements for Mac: Macintosh with MacOS X or later; 128 MB RAM or more; DVD-ROM drive; 450 MB free space on the hard disk; graphics system with 1024x768 pixel resolution at 24 bit color depth (True Color); speakers; Safari Web Browser; Sun Java version 1.5 for MacOS X.
Keywords: Endodontics